PENERAPAN METODE BAYES DALAM MENDIAGNOSA GANGGUAN PERKEMBANGAN PADA ANAK - Rita Hamdani (Jurnal Mantik Penusa, 2016)
Children are the individuals who are in a range of developmental changes starting from infants to teenagers. Childhood is a time of growth and development. Child development can be fast or slow depending on these factors. But what if the child's development is not as prevalent as thumb sucking, nail biting, head banging, biting or hitting herself, shaking, emotional changes, such behavior like anger venting frustration or upset about something. With the proliferation of computers today. The problems above can be used to help parents detect whether a child has a disorder or not is by using expert system (Expert System). Expert system menggandung specific knowledge so that any common man to use it to solve a specific problem. Design Expert System Diagnosis Developmental disorders in children with methods of Bayes, which is a process of inference that starting the search from the input data in the form of symptoms led to the conclusion that the conclusions by providing a solution to the suggestions based on the symptoms observed, aims to conduct consultations without having to meet doctor costly and time. This application is created by using Visual Basic .Net 2010 and SQL Server 2008. The application is built equipped with a knowledge management system that is easy to use and dynamic.